Impact of PARP inhibitor maintenance therapy in newly diagnosed advanced epithelial ovarian cancer: A meta-analysis. - Banghyun Lee; Suk-Joon Chang; Byung Su Kwon; Joo-Hyuk Son; Myong Cheol Lim; Yun Hwan Kim; Shin-Wha Lee; Chel Hun Choi; Kyung Jin Eoh; Jung-Yun Lee; Dong Hoon Suh; Yong Beom Kim (PLoS ONE)
Objectives This meta-analysis was undertaken to systematically evaluate the effects of poly (ADP-ribose) polymerase inhibitor (PARPi) maintenance therapy on the survival of newly diagnosed advanced epithelial ovarian cancer (EOC) patients. Methods/materials A systematic literature search revealed 3,227 studies. A subsequent selection process identified seven suitable randomized studies that assessed the survival outcomes in newly diagnosed advanced EOC patients administered PARPi (n = 1921; the PARPi group) or placebo (n = 1150; the placebo group). The survival outcomes were compared with respect to the PARPi treatment regardless of bevacizumab maintenance therapy. All adverse events ≥ grade 3 were analyzed. Review Manager Version 5.4.1 software was used for the meta-analysis. Results The two-year progression-free survival (PFS) was significantly better in the PARPi group than the placebo (Hazard ratio [HR], 0.53; 95% confidence interval [CI], 0.41 to 0.68). Furthermore, patients in the PARPi group with the BRCA1/2 mutation (BRCAm), BRCA wild type, homologous-recombination deficiency (HRD), or HRD without BRCAm, but not with homologous-recombination proficiency had a significantly better two-year PFS than the patients in the placebo group. The five-year overall survival (OS) was comparable in the two groups, but patients in the PARPi group with BRCAm had a significantly better five-year OS than those in the placebo group (HR, 0.57; 95% CI, 0.44 to 0.74). In addition, the adverse event rate (≥ grade 3) was significantly higher in the PARPi group than in the placebo group (HR, 2.94; 95% CI, 1.13 to 7.63). Conclusions In patients with newly diagnosed advanced EOC, PARPi maintenance therapy was significantly more effective in terms of survival than no PARPi treatment. However, the risk of serious adverse events was higher for patients who received PARPi maintenance therapy.